MSMEs Understanding of Taxation During the COVID-19 Pandemic - Neneng Susanti; Vincentia Wahju Widajatun (Faculty of Smart Technology and Engineering, Universitas Kristen Maranatha, Bandung, Indonesia, 2021)
This paper based on a community service activities held with the aim of providing an understanding of government policies in providing tax incentives; understanding of the period of payment, deposit and tax reporting; and calculation of PPh (income tax). The implementation of the community service was carried out using lecture, tutorial, and discussion methods. Activity material prepared regarding the introduction of taxes during pandemic in order to help MSMEs in dealing with the impact of COVID-19 with hope of providing understanding for MSMEs which can later be applied and transmitted to the wider community. The target of PKM counselling activities, those who participated, understood the material provided. Their understanding were quite good, it was seen from the questions asked and discussions quality of the participants. By understanding the material from this information dissemination activity, it is expected that MSMEs assisted by KADIN in the culinary and fashion sectors can do better planning in terms of financial strategies related to taxation policies during the pandemic.